DOOR ALARM CIRCUITS USING ULTRASONIC SENSOR - Faisal Nurdinsyah; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Komputer, 2008)
In an age of globalization today's advanced technology development appears rapidly.This was evident in the electronics world is increasingly widespread due to theeducational world that has begun to peel and conduct various tests, so that it can be areference This elektronic. This paper trying to introduce something a door alarmwhich in applying this tool to use component - components are known or frequentlyused include ultrasonic transducers, transmitters, and receiver. This tool can beinstalled in front of the fence or at the door with a concealed position in order noteasy to know other people.